Analisis Proses Dan Perlakuan Akuntansi Pembiayaan Akad Rahn Tasjily (Studi Kasus PT. XYZ) - Hakim, Muadz Abdul; Hendra, Grandis Imama (IAIN Kudus, 2022)
The research aims to determine the process and accounting treatment of the financing by Rahn Tasjily Contract. The method used is a Descriptive Case Study on PT XYZ. The analysis used theoretical propositions as a general strategy and pattern matching as a specific analysis. It consists of primary data (interviews and observations) and secondary data (contracts, accounting treatment in the system, PT XYZ annual reports, DSN-MUI fatwa, and PSAK). The study results indicate that the process of financing the Rahn Tasjily contract is under the fatwa by DSN-MUI. The financing contract begins with the Qardh contract and then continues with the Rahn Tasjily Contract to collect maintenance services fee / Mu’nah, accounting treatment of the financing by Rahn Tasjily contract is related to financial accounting standards by IAI. Still, it is not following PSAK Ijarah/Sharia Rent because the characteristics of the Rahn Tasjily are fee-based services. This study impacts the institution’s compliance in carrying out rahn tasjily financing of PSAK 107 (Effective 1 January 2017) and Fatwa DSN MUI DSN No.92/DSN-MUI/III/2014 for financing by Rahn Tasjily Contract.